DIMENSIONAL ACCURACY OF PROTOTYPES MADE WITH FDM TECHNOLOGY - Tomić, Davor; Fudurić, Ana; Mihalić Tihomir; Šimunić Nikola (Journal of Energy Technology, 2024)
Under the term “additive manufacturing”, commonly known as 3D printing, we distinguish various methods of manufacturing technologies. Common to all these processes is manufacturing a model layer by layer from a digital form. The aim of this paper is to experimentally determine which material provides dimensionally more accurate prototypes on a Fused Deposition Modelling (FDM) additive machine. Acrylonitrile Butadiene Styrene (ABS) and PolyLactic Acid (PLA) materials were used. The di- mensional accuracy was checked by comparing the Computer-Aided Design (CAD) model with each of ten models obtained by the method of 3D scanning. The results show that prototypes manufactured from PLA are dimensionally more accurate those made from ABS.